PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI POLINOMIAL BERBANTUAN APLIKASI GEOGEBRA UNTUK SISWA KELAS XISMA NEGERI 2 KEPULAUAN TANIMBAR - Bakker, Julita; Ratuanik, Mesak; Nifmaskossu, Regina (Leibniz: Jurnal Matematika, 2025)
Learning technology is used in education so that it can be used as a change in the delivery of teaching and learning in schools from conventional learning to unconventional learning. The purpose of this study is to determine the use of a problem-based mathematical learning model assisted by geogebra application to improve mathematical problem-solving skills in polynomial materials for grade XI students of SMA Negeri 2 Tanimbar Islands. The methodology used in this study is descriptive qualitative research. There are three ways that researchers use to obtain data, namely: tests, interviews and documentation. The data analysis techniques in this study are data collection, data reduction, data presentation, and conclusion drawn. The results of this study are that from the three problems given at the time of the final test which was attended by 26 students, there were 20 students who had more dominant problem solving abilities, namely being able to identify known and asked aspects and determine whether these aspects were sufficient to solve the problem. Combining the components that have been asked and known and formulating them into a mathematical model, choosing a method to solve the problem, working together to solve mathematical problems and confirming that the answer is correct and accurate, but there are 6 students who still find it difficult to sketch polynomial function graphs correctly. manually. Meanwhile, for proof using the Geogebra application, all students in class So the use of a problem-based mathematics learning model assisted by the Geogebra application can improve mathematical problem solving abilities in polynomial material for class XI students at SMA Negeri 2 Tanimbar Islands.